Mixed methods research - Watkins, Daphne; Gioia, Deborah (New York Oxford University Press, 2015)
"Finally, a practical guide to mixed methods research has been written with health and human services professionals in mind. Watkins and Gioia review the fundamentals of mixed methods research designs and the general suppositions of mixed methods procedures, look critically at mixed method studies and models that have already been employed in social work, and reflect on the contributions of this work to the field. But what is most important is that they lead the reader through considerations for the application of the mixed methods research in social work settings. The chapters of this book are structured so that readers can (figuratively) walk through the mixed methods research process using nine steps. Chapters one, five, and six provide supplemental material meant to serve as grounding for chapters two, three, and four, which outline nine steps in the mixed methods research process, and specific to social work research. This is a short and practical guide not just for learning about mixed methods research, but also doing it"--Provided by publisher.
"In this pocket guide, Watkins and Gioia review the fundamentals of mixed methods research designs and the general suppositions of mixed methods procedures; look critically at mixed method studies and models that have already been employed in social work; and reflect on the contributions of and application of this work to the field"-- Provided by publisher.
Machine generated contents note: -- Preface -- Chapter 1 (First Floor): An Introduction to a "Mixed" Way of Thinking -- Chapter 2 (Second Floor): Designing Mixed Methods Studies in Social Work -- Step 1: Develop your purpose statement and research questions -- Step 2: Understand mixed methods language and notation -- Step 3: Choose a mixed methods design -- Chapter 3 (Third Floor): Mixed Methods Data Collection in Social Work -- Step 4: Decide on the data collection methods needed -- Step 5: Develop your sampling plan and recruitment strategies -- Step 6: Collect the data -- Chapter 4 (Fourth Floor): Mixed Methods Data Analysis in Social Work -- Step 7: Prepare the data for analysis -- Step 8: Analyze the data -- Step 9: Interpreting your integrated findings -- Chapter 5 (Fifth Floor): Perils, Pitfalls and Considerations -- Chapter 6 (Sixth Floor): Writing up, Presenting, and Teaching Mixed Methods -- References.
Includes bibliographical references (pages 171-179) and index.
Keywords: Social service -- Research; Research -- Methodology